The Influence of Promotion, Celebrity Support, E-WOM (Electronic Word of Mouth) and Halal Awareness on Purchasing Decisions for Skincare Product at Marketplace in East Java - Lita Marshella Fitriani; Rizky Eka Febriansah; Rita Ambarwati Sukmono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The influence of promotions, celebrity endorsements, E-WOM (Electronic Word of Mouth), and halal awareness plays an important role in influencing purchasing decisions for skincare products in the East Java marketplace. Promotions, celebrity endorsements, E-WOM (Electronic Word of Mouth), and halal awareness are factors that influence consumers' decisions to make purchases. This research aims to determine the influence of promotions, celebrity endorsements, E-WOM (Electronic Word of Mouth), and halal awareness on purchasing decisions for skincare products on marketplaces in East Java. This research method uses descriptive analysis with a quantitative approach. Primary data was obtained by sharing the questionnaire link using Google Form. The data analysis technique uses Partial Least Square 4.0. The results of this research show that promotions, celebrity endorsements, E-WOM (Electronic Word of Mouth), and halal awareness have a positive and significant effect on purchasing decisions.